ANTESEDEN REPURCHASE INTENTION: STUDI EMPIRIS PADA KONSUMEN VITAMIN C SAAT PANDEMI COVID-19 DI JAKARTA - Vita Briliana; Guniadi Fialim (Jurnal Bisnis dan Akuntansi, 2023)
This study aims to examine and analyze how the influence of Brand Trust, Perceived Value and Halal Concern on Brand Preference and Satisfaction and their consequences on Repurchase Intention of consumers of vitamin C products in Jakarta. This research design uses descriptive and causal research by measuring all variables using a Likert scale consisting of 5 points. The sampling technique used was the purposive sampling method which was carried out by distributing questionnaires to 281 respondents. Statistics for data processing with the Structural Equation Model (SEM) analysis method used in this study are SmartPLS version 3.0 and IBM SPSS. The results of this study explain that Brand Trust, Perceived Value and Halal Concern affect Brand Preference and Satisfaction. It was identified that Halal Concern had the most influence on Brand Preference and Satisfaction. Meanwhile, Brand Preference has a higher impact than Satisfaction on Repurchase Intention on vitamin C consumers in Jakarta. The implication of this research is vitamin C producers should register their products to get halal certificate to increase their sales.